Some surface singularities obtained via Lie algebras - Nakamoto, K.; Tosun, M.; Tosun, M. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2007)
In this work, we present a relation between a special six dimensional Lie algebra and the simple elliptic singularities of type (D) over bar (5).
Keywords: simple elliptic singularities; lie algebras; Mathematics